Evaluating the performance of Inspector General Office of the Ministry of health in accordance with normative people and people results for the European excellence model EFQM 2013 - صيهود, علي موات; حيدر, زيد علي (Journal of Economics and Administrative Sciences, 2017)
Abstract:Current research has sought to apply the criteria of potential for altmizalaorbi model EFQM 2013 in assessing the performance of the Inspector General's Office/Ministry of health, so as to keep up with a modern and advanced management methods in the evaluation of performance, as well as to link performance to a citizen's life, and it takes him beyond the accepted service capabilities today, but of budget duties between dealers servicing responsibilities and future planning, financial control, competitiveness, human resources needs and maintaining quality and development, as well as the constant quest for continuous improvement, is the spirit of the principle underpinning the European Foundation Quality management when designing a model of excellence.  Use the Finder method of applied research, through data collection checklist for evaluation in addition to interviews, the answer has been analysed using percentages and arithmetic, and indicate their strengths for the purpose of strengthening, and vulnerabilities for patch and calendar, and improvement opportunities to invest and not to be missed. The outcome of the evaluation of potential standards generally good results except standard leadership, where criterion driving 57 points out of 100 points allocated